Plant communities along the Eerste River, Western Cape, South Africa: Community descriptions and implications for restoration - Meek, C.; Richardson, D.; Mucina, Ladislav (AOSIS, 2012)
Riparian plant communities fulfil many functions, including the provision of corridors linking protected areas and other zones of high conservation value. These habitats across much of South Africa’s Cape Floristic Region, especially in the lowlands, have been heavily impacted and degraded by human activities. There is increasing interest in the restoration of degraded riparian zones and the ecosystem services they provide to enhance the conservation value of landscapes. Previous studies of riparian vegetation in the Cape Floristic Region focused on pristine headwater systems, and little is known about human-impacted communities that make up most of the riparian vegetation in downstream areas. More information is needed on the composition of these plant communities to establish a baseline for management intervention.The riparian zone of the Eerste River in South Africa’s Western Cape province provides a good opportunity to study the features of riparian vegetation along the entire gradient, from pristine vegetation in a protected area through different levels of human-mediated degradation. Riparian vegetation was surveyed in 150 plots along the entire length of the Eerste River (ca. 40 km). Data were analysed using the vegetation classification and analysis software package JUICE. Final groupings were plotted onto a two-dimensional detrended correspondence analysis plane to check the position of the communities in the reduced multidimensional space. Ten distinct plant communities were identified, including several novel communities dominated by alien plant species. Descriptions of each plant community are presented. Diagnostic, constant and dominant species are listed and the major structural and ecological characteristics of each community are described. Conservation implications: Major changes to hydrological and soil properties, nutrient dynamics and disturbance regimes and plant species composition along sections of the riparian zone mean that restoration of many of these habitats to their historic condition is not feasible. However, several native plant species that provide key ecosystem services persist in and adjacent to transformed communities, offering substantial opportunities for restoration to achieve certain goals.